Alcohol abuse increases the risk of HIV infection and diminishes health status of clients attending HIV testing services in Vietnam. Issue 1 (December 2016) - Tran, Bach; Nguyen, Long; Nguyen, Cuong; Phan, Huong; Latkin, Carl
Abstract Background Vietnam is among those countries with the highest drinking prevalence. In this study, we examined the prevalence of alcohol use disorders (AUDs) and its associations with HIV risky behaviors, health care utilization, and health-related quality of life (HRQOL) among clients using voluntary HIV testing and counseling services (VCT). Methods A cross-sectional survey of 365 VCT clients (71 % male; mean age 34) was conducted in Hanoi and Nam Dinh province. AUD and HRQOL were measured using the Alcohol Use Disorders Identification Test-Consumption (AUDIT-C), and EuroQol-five dimensions-five levels (EQ-5D-5L). Risky sexual behaviors, concurrent opioid use, and inpatient and outpatient service use were self-reported. Results 67.2 % clients were lifetime ever drinkers of those 62.9 % were hazardous drinkers and 82.0 % were binge drinkers. There were 48.8 % respondents who had ≥2 sex partners over the past year and 55.4, 38.3, and 46.1 % did not use condom in the last sex with primary/casual/commercial sex partners, respectively. Multivariate models show that AUD was significantly associated with risky sexual behaviors, using inpatient care and lower HRQOL among VCT clients. Conclusions AUD was prevalent, was associated with increased risks of HIV infection, and diminished health status among VCT clients. It may be efficient to screen for AUD and refer at-risk clients to appropriate AUD counseling and treatment along with HIV-related services.